Vibration strength estimation of a structure-borne source: Case study for a reception beam - Putra, Azma; Saari, Noor Fariza; Bakri, Hairul; Ramlan, Roszaidi (Trans Tech Publications, 2014)
This paper presents the estimation of vibration strength obtained from reception structure method. It describes a laboratory-based measurement procedure, which determines the strength of a vibration source in terms of its total squared free velocity. The source used in the experiment is a small electric fan motor. Here instead of using the usual flat rectangular plate, a thin stainless steel beam was used as the reception structure. The aim is to validate the data obtained from the reception method with that from the direct measurement. A good agreement is found between the two results, although small discrepancies occur due to the modal behavior of the beam.